Harnessing de-oiled Glycine max seed-anchored-CuO nanoparticles for adsorptive removal of crystal violet dye with comprehensive mechanistic insights - Usman, Mahnoor; Batool, Fozia; Iqbal, Tunzeel; Noreen, Sobia; Gondal, Humaira Yasmeen; Roheen, Taleeha; Qadir, Rahman; Amin, Muhammad; Sajid, Sayyam; Ditta, Allah (Royal Society of Chemistry, 2025)
A novel solution is introduced by harnessing the power of de-oiled Glycine max L. seeds (DO/S) and enhancing them with copper oxide-loaded nanoparticles (DO/S NPs) to effectively eradicate the toxic dye crystal violet (triarylmethane dye) from aqueous solutions. The presence of peaks at 653.87 cm−1 and 567.07 cm−1 in FTIR spectra confirmed the presence of CuO NP loading on G. max L. seeds. Furthermore, the smooth spherical cavities facilitated crystal violet adsorption, as revealed by SEM analysis. PZC results revealed that adsorption is more efficient under neutral and basic conditions (pH 7, 9, and 11) for DO/S, whereas DO/S NPs as an adsorbent facilitate excellent crystal violet removal in basic media (pH 9 and 11). Thermogravimetric analysis showed that major weight loss occurs at 21.49 min, 446 °C (DO/S), and at 22.64 min, 467.47 °C (DO/S NPs). Thermodynamics studies revealed less randomness, spontaneity, and favorable adsorption reactions by the copper-loaded adsorbent. Kinetics studies showed that the employment of a pseudo-second-order kinetic model efficiently fitted the obtained experimental data (R2 ≥ 0.99). A batch experiment was performed by applying varying adsorption parameters. In comparison to DO/S, DO/S NPs exhibited an improved maximum removal rate, i.e. a rate of 95% at a dye concentration of 80 ppm, a contact time of 90 minutes, 293.15 K, pH 9, and an adsorbent dose of 1 g. Since de-oiled G. max L. is an industrial byproduct, its potential as an adsorbent for textile dye removal is an effective approach toward a clean environment for future generations.